Post-infectional biochemical changes in maize leaves affected by banded leaf and sheath blight disease - M.K. KHOKHAR*; K.S. HOODA, VINITA DAHIMA, S.S. SHARMA (Indian Phytopathology, 2014)
Total phenol content, peroxidase and polyphenol oxidase contents were estimated in maize germplasm affected by banded leaf and sheath blight disease. In comparison to healthy plants, the increase in total phenol content in diseased plants was maximum in extra early germplasm (362.3%) followed by inbreds (353.06%). Contrarily, peroxidase level increase was maximum in early maturity germplasm (87.5%) followed by inbred (86.0%). The relative increase in polyphenol oxidase was maximum in early maize germplasm (70.8%) followed by inbreds (63.7%). These are secretions which require trigger by means of pathogen attack, elicitor response and abiotic stresses. It appears that higher phenol, peroxidase and polyphenol oxidase activities in maize germplasm plays a vital role in inducing resistance against banded leaf and sheath blight (BLSB) disease in maize.